Qualitative research for education : An introduction to theory and methods - Bogdan, Robert; Biklen, Sari Knopp (Boston : Allyn and Bacon, 1992)
Contains examples from studies illustrating the various steps of a fieldwork project from design to analysis and writing. The text aims to combine accessibility with conceptual sophistication.
Includes bibliographical references.
Keywords: Education -- Research